PENGEMBANGAN MEDIA PEMBELAJARAN WAYANG CUCOK UNTUK MENINGKATKAN KEMAHIRAN AL-KALĀM - Naili Vidya Yulistyana; Sri Sumarni (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2016)
This paper describes the efforts to improve the skills of kalām in students of class XI of MAN 1 Jepara through the developed Wayang Cucok Arabic language learning media. The enhancement of kalām proficiency in students which is being developed is on the placement of emphasis/stress, makharijul huruf (pronunciation), sentence intonation, fluency, and courage. With R & D Research Methods, the data were analyzed by quantitative descriptive analysis. The assessment of the experts in FGD forum on content feasibility aspect is 3, 58 (very good), language feasibility aspect is 3.44 (excellent), contextual valuation aspect is 3.38 (very good), feasibility aspects of presentation is 2, 88 (good), physical aspect of media is 3,10 (very good), and audio aspect is 2,92 (good). While the results of the test show that the kalām skills in students keep increasing in each meeting; the pretest score shows the mean of 63, 4 while the post test has an average value of 82.0. The t test shows the results of -17, 51 which can be interpreted that the media used is effective and acceptable at level of 99%.